PREDICTORICAL VALUES OF BASIC - MOTORICAL ABILITIES AND RELATIONS OF MOTORICAL INFORMATIONS IN VOLLEYBALL AT 15 YEAR OLD PUPILS - Bećir Šabotić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
Now days, it is known an enormous number of games which regularly organize sport competitions. The most popular of them are included into the program of the Olympic Games, where volleyball takes very important place because of its wide use. Volleyball is a sport of higher achievement (first class sport), sport fun as well as the important means of active rest and recovery (of recreation) and of course one of the most powerful means of physical education. Subject and the goal of research By the logics of the problem that is being researched, as the subject of the research it is taken the substructure of anthropological status as basically-motorical abilities.Starting from the research problem, the goal of this work is to establish the connection between predictorical variables of the basically-motorical abilities on one hand and the variables of criterion of situationally-motorical informations in volleyball on the other hand. Hypothesis There is very important connection between the set of predictorical variables of basically- motorical abilities and the set of variables of criterion of situationally-motorical informations in volleyball.The sample of those who are being questioned The population from which the sample is taken defines itself as a population of pupils of the first grade of the high schools whose age is 15 +/- 6 months. The total sample of those who are being questioned was 420 pupils-men. The conclusion By getting the final results, the conclusion would be that those who are being questioned, with better speed, better coordination and with bigger explosive strength, will have better results in tests of performing specific motorics in volleyball. Results like this are logical in consideration of the structure while performing the exercises in volleyball, which demand speed, good coordination of moves as well as the limited level of strength